Edukasi Pemanfaatan Tanaman Obat Indonesia untuk Penyakit Degeneratif di Meruyung-Depok - Rahmi, Eldiza Puji; Muti, Annisa Farida; Revina, Rika; Citra Pradana, Dhigna Luthfiyani (Universitas Pahlawan Tuanku Tambusai, 2025)
Currently, degenerative diseases have become a problem for every country throughout the world, including Indonesia. The use of medicinal plants in the surrounding area to prevent degenerative diseases is one strategy to improve public health. This Community Service Activity aims to educate the public in recognizing and utilizing medicinal plants to prevent degenerative diseases. This activity was carried out at the UPNVJ Meruyung Housing Complex, Depok. The method used was community education through counseling by providing explanations about degenerative diseases, conducting socialization of types of medicinal plants, their benefits and applications, in addition the level of knowledge of participants was also measured using questionnaires for pre- and post-tests. This activity was attended by the community, especially women at the UPNVJ Meruyung Depok Housing Complex. The results of the activity provided knowledge about degenerative diseases and the use of Indonesian medicinal plants for degenerative diseases. The knowledge and understanding of the community about degenerative diseases and recognizing and utilizing medicinal plants increased significantly (p 0.001) after the activity by 61.36%.